Aptamer Combined with Fluorescent Silica Nanoparticles for Detection of Hepatoma Cells - Zixi Hu; Juntao Tan; Zongqiang Lai; Rong Zheng; Jianhong Zhong; Yiwei Wang; Xiaoxue Li; Nuo Yang; Jieping Li; Wei Yang; Yong Huang; Yongxiang Zhao; et al. (Nanoscale Research Letters)
Abstract Purpose The purpose of this study is to develop a simple, effective method to label hepatoma cells with aptamers and then detect them using fluorescent silica nanoparticles (FSNPs). Method Streptavidin was conjugated to carboxyl-modified fluorescein isothiocyanate (FITC)-doped silica nanoparticles which were prepared by the reverse microemulsion method. The resulting streptavidin-conjugated fluorescent silica nanoparticles (SA-FSNPs) were mixed with hepatoma cells that had been labeled with biotin-conjugated aptamer TLS11a (Bio-TLS11a). The specificity and sensitivity of the nanoprobes were assessed using flow cytometry and fluorescence microscopy. Their toxicity was assessed in normal human liver cell cultures using the MTT assay, as well as in nude mice using immunohistochemistry. Results SA-FSNPs showed uniform size and shape, and fluorescence properties of them was similar to the free FITC dye. SA-FSNPs were able to detect aptamer-labeled hepatoma cells with excellent specificity and good sensitivity, and they emitted strong, photobleach-resistant fluorescent signal. SA-FSNPs showed no significant toxic effects in vitro or in vivo. Conclusion The combination of biotin-conjugated aptamers and SA-FSNPs shows promise for sensitive detection of hepatoma cells, and potentially of other tumor cell types as well.